1991
DOI: 10.1080/15287399109531580
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic study of cadmium and lead in the hair of ceramists and dental personnel

Abstract: Ceramists may be exposed to heavy metal-containing dusts and vapors, especially when working with colored glazes. Because cadmium- and lead-containing glazes are commonly used, an epidemiologic study of the hair content of these metals among 70 ceramists in central New York was conducted. A comparably aged group of 75 dentists and orthodontists in the same geographic area was used as the control cohort. The median levels of both metals in the hair of the ceramists were significantly higher than those among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Besides, there is a study that showed the geometric mean for HLL of the ceramic plant workers (7.6 µg/g) was significantly higher than the persons who did not expose to lead (3.2 µg/g) (Strumylaite et al, 2004). Similar findings have been revealed in other studies (Bache, Lisk, Scarlett, & Carbone, 1991;Zaborowska, Wiercinski, & Maciejewska-Kozak, 1989). The direct exposed to lead of exposed group while working might also be the main reason of this finding.…”
Section: Hair Lead Level (Hll)supporting
confidence: 81%
“…Besides, there is a study that showed the geometric mean for HLL of the ceramic plant workers (7.6 µg/g) was significantly higher than the persons who did not expose to lead (3.2 µg/g) (Strumylaite et al, 2004). Similar findings have been revealed in other studies (Bache, Lisk, Scarlett, & Carbone, 1991;Zaborowska, Wiercinski, & Maciejewska-Kozak, 1989). The direct exposed to lead of exposed group while working might also be the main reason of this finding.…”
Section: Hair Lead Level (Hll)supporting
confidence: 81%
“…Evidence accumulated since the late 80s suggests that hazardous airborne contaminants are emitted from the ring of ceramics. [26][27][28] Hirtle et al (1998) 29 have reported that signicant amounts of metals are present in the total suspended particulate matter emitted during the ring of ceramics. These measurements can explain the ndings of Hibbert et al (1999) 30 and later of Jones et al (2013) 31 who showed that signicant amounts of heavy metals are present in the blood of artisanal pottery workers.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence accumulated since the late 80s suggests that hazardous airborne contaminants are emitted from the ring of ceramics. [26][27][28] who showed that signicant amounts of heavy metals are present in the blood of artisanal pottery workers. Albeit the importance of these ndings, to the best of our knowledge, no information on the size distribution or the size-resolved composition of the emitted particles is available.…”
Section: Introductionmentioning
confidence: 99%